2015
DOI: 10.1155/2015/481739
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study and Thermal Decomposition Behavior of Lignite Coal

Abstract: A thermogravimetric analyzer was employed to investigate the thermal behavior and extract the kinetic parameters of Canadian lignite coal. The pyrolysis experiments were conducted in temperatures ranging from 298 K to 1173 K under inert atmosphere utilizing six different heating rates of 1, 6, 9, 12, 15, and 18 K min −1 , respectively. There are different techniques for analyzing the kinetics of solid-state reactions that can generally be classified into two categories: model-fitting and model-free methods. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 31 publications
3
67
0
1
Order By: Relevance
“…However, the differential method of Friedman can eliminate this error. Thus, the Friedman method can be regarded as the best method to evaluate the kinetic parameters compared with other model-free methods such as KAS and FWO [31][32][33][34]. For SYIM and EGIM, the activation energy varied significantly at the higher degree of conversions, indicating the existence of a complex multi-step mechanism including parallel, competitive, and consecutive reactions and activation energies [35].…”
Section: Calculation Of the Activation Energy According To The Model-mentioning
confidence: 99%
“…However, the differential method of Friedman can eliminate this error. Thus, the Friedman method can be regarded as the best method to evaluate the kinetic parameters compared with other model-free methods such as KAS and FWO [31][32][33][34]. For SYIM and EGIM, the activation energy varied significantly at the higher degree of conversions, indicating the existence of a complex multi-step mechanism including parallel, competitive, and consecutive reactions and activation energies [35].…”
Section: Calculation Of the Activation Energy According To The Model-mentioning
confidence: 99%
“…The final devolatilisation zone is observed where the fixed carbon and ash are released. According to Heydari et al (2015), the lower devolatilisation rates observed can attribute to further gasification and char released at elevated temperatures.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…In this study, kinetic pyrolysis is applied to the two most dominant disposable diaper brands in South Africa (Huggies and Pampers) in order to assess their potential of waste-to-energy production. Pyrolysis involves the thermochemical treatment of samples in the absence of oxygen at elevated temperatures, and during this process, multiple reactions occur, (Apaydin-Varol et al, 2014, Heydari et al, 2015, Perera and Narayana, 2018. In addition, pyrolysis is also known for its production of pyro-gas, pyro-oil, and pyro-char (Heydari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By plotting ln(t) with respect to 1/T, the activation energy can be obtained for a given value of from the slope of the regression line if at least three isothermal temperatures are explored. The application of this approach provides a means of estimating the overall activation energy associated with the process [99].…”
Section: Kinetic Model Representation Approachmentioning
confidence: 99%